ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK BUMN DAN BANK SWASTA DENGAN METODE RGEC - Lulu Amalia Nusron (JURNAL FAIRNESS, 2023)
The research aims to determine the assessment of the soundness level of state-owned banks and private banks book IV using the RGEC method during 2015-2019. The population of this research is all banks registered with the Financial Services Authority. This research is descriptive with a quantitative approach. The sample performance in this research used purposive sampling technique with certain criteria. The criteria are 1) The sample conventional commercial banks & state-owned enterprises are those included in book IV in 2015 - 2019. 2) National private banks & state-owned enterprises with core capital of more than 30 trillion & included in book IV during 2015-2019. 3) State-owned banks and conventional banks with a ratio of large and small core capital that are proportional to the value of the analysis method used is the different test with the independent sample test. The results of this research on the health assessment of the bank show that the NPL, LDR and ROA ratios are significant differences between private banks IV and state-owned banks, while for GCG, CAR and NIM there is no significant difference between the soundness level of state- owned banks and private banks BUKU IV.